If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0.5(8x + 12) = 6x Reorder the terms: 0.5(12 + 8x) = 6x (12 * 0.5 + 8x * 0.5) = 6x (6 + 4x) = 6x Solving 6 + 4x = 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 6 + 4x + -6x = 6x + -6x Combine like terms: 4x + -6x = -2x 6 + -2x = 6x + -6x Combine like terms: 6x + -6x = 0 6 + -2x = 0 Add '-6' to each side of the equation. 6 + -6 + -2x = 0 + -6 Combine like terms: 6 + -6 = 0 0 + -2x = 0 + -6 -2x = 0 + -6 Combine like terms: 0 + -6 = -6 -2x = -6 Divide each side by '-2'. x = 3 Simplifying x = 3
| factorm^8n^2-n^18-m^8+n^16=0 | | 62x+21=32x+23 | | log(3)(5x-1)=1 | | 92x+42=26x+18 | | x+2.35=9.78+x+7.22 | | 25x+17=14x+3 | | 6+5x-6x=-2 | | 24x^2+92x+80= | | 15x+6=12x+4 | | 3cos^2x+5sinx=4 | | 3x^2-29x-7=0 | | 1.5(x+8)=7.2+.9x | | 9.75-18=5.25 | | 4n^2-24n= | | 2.5x-15=12.5 | | q+-4=12 | | B+2.35=9.78+b+7.22 | | -10x-16y=-18 | | 4x^2-20x+21= | | 2x-10+x-40=180 | | x^2+42=70 | | 5-3x=-8x+5 | | 0=-x^2+13x-36 | | 2x-(x+1)=-2x+21 | | 6a^2-31a+28= | | h(h-1)/2h | | (4/5)*(1/6)= | | -2x+17=-13 | | (6/5x)-(8/5) | | 2ln(x)-3=-1 | | 2x-x=x-x+9 | | X=(6/5)x-(8/5) |